Divergencias y antagonismos del movimiento social indígena en la Región de Arica y Parinacota (1965-1985) - Carlos Choque Mariño (Confluenze, 2009)
This article analyzes the differences and antagonisms of the indigenous social movement in northern Chile between the years 1965 to 1985. The study tries to unravel the origins and languages of indigenous organizations that have deconstructed their ethnic identity from cultural diversity, nationalism and political processes that have affected during this period.